A water soluble ESIPT-based fluorescent chemodosimeter for the ratiometric detection of palladium ions in aqueous solution and its application in live-cell imaging. (28th August 2018) - Huang, Jing; Ding, Yu; Fu, Hongyu; Chen, Bo; Han, Yifeng
Abstract : A new Excited State Intramolecular Proton Transfer (ESIPT) based water-soluble fluorescent chemodosimeter for the ratiometric detection of palladium ions has been rationally designed and developed. Abstract : An Excited State Intramolecular Proton Transfer (ESIPT) based water-soluble fluorescent chemodosimeter for the ratiometric detection of palladium ions has been rationally designed and developed. Based on the specific reactivity of palladium-promoted hydrolysis, the probe exhibited high selectivity and sensitivity towards palladium ions. Furthermore, the probe was successfully used for fluorescence imaging of Pd 2+ in living cells.